DIFFERENTIATION BETWEEN PORCINE AND BOVINE GELATIN IN CAPSULE SHELLS BASED ON AMINO ACID PROFILES AND PRINCIPAL COMPONENT ANALYSIS - Widyaninggar, Amalia; ., Triwahyudi; Triyana, Kuwat; Rohman, Abdul (Indonesian Journal of Pharmacy, 2012)
Gelatin  used  for  capsule  shells  can  be  derived  from porcine  origin.  Some  religion  like  Islam  prohibited  their followers  to  consume  any  products  containing  porcine derivatives  including  porcine  gelatin  in  the  products. Consequently,  some  rapid  and  reliable  techniques  are continuously  developed  for  detection  of  porcine  gelatin  in some pharmaceutical products like  capsule shells. The aim of this study was to evaluate the possibility to use  amino acid profile  in  combination  with  chemometrics  of  principal component  analysis  for  detection  and  classification  between gelatin in capsule derived from porcine and bovine. Based on score  plot  of  first  principal  components  (PC1)  and  second principal  components  (PC2),  porcine  and  bovine  gelatins  in capsule could be apparently distinguished.Key  words:  bovine  gelatin;  porcine  gelatin;  amino  acid  profile; principal component analysis